Comprehensively Understanding the Transformation of Paramagnetic Tetramer to Spin-Paired Dimer in an S = ½ Molecular Crystal - Yin Qian; Yan Gao; Lei Xu; Reinhard K. Kremer; Jin Zhang; Xiao-Ming Ren (Magnetochemistry)
In this study, we comparatively analyzed the variable-temperature crystal structures for two isomorphous salts, [1-benzyl-4-aminopyridinium][M(mnt)2] (M = Ni or Cu; mnt2− = maleonitriledithiolate; labeled as APy-Ni or APy-Cu). Both salts crystallize in the triclinic P–1 space group at 296 K, comprising linear [M(mnt)2]− (M = Ni or Cu) tetramers. A magnetostructural phase transition occurs at TC~190 K in S = ½ APy-Ni at ambient pressure, with a conversion of paramagnetic tetramers into nonmagnetic spin-paired dimers. The discontinuous alteration of cell parameters at TC signifies the characteristic of first-order phase transition in APy-Ni. No such transition appears in the nonmagnetic APy-Cu within the same temperature vicinity, demonstrating the magnetic interactions promoting the structural phase transition in APy-Ni, which is further reinforced through a comparison of the lattice formation energy between APy-Ni and APy-Cu. The phase transition may bear a resemblance to the mechanisms typically observed in spin-Peierls systems. We further explored the magnetic and phase transition properties of APy-Ni under varying pressures. Significantly, TC shows a linear increase with rising pressure within the range of 0.003–0.88 GPa, with a rate of 90 K GPa−1, manifesting that the applied pressure promotes the transition from tetramer to dimer.